2019
DOI: 10.1111/roie.12394
|View full text |Cite
|
Sign up to set email alerts
|

Do trade flows respond to nudges? Evidence from the WTO’s Trade Policy Review Mechanism

Abstract: Relatively little is known about the economic effects of WTO members’ communications outside of official negotiations and dispute proceedings. This paper considers whether interactions between members through the Trade Policy Review Mechanism, the WTO’s prime transparency institution, lead to subsequent changes in bilateral trade flows. Trade policy concern submissions are more likely to lead to positive trade responses when (i) the receiving country is less concerned about terms‐of‐trade losses, (ii) the subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…In explaining the existence of TPRB, Kuenzel (2019) asserted that the TPRB Review could not be qualified as a product that effectively contributes to the reviewed member. The Annex 3A of the WTO Agreements confirms it by stipulating that: Therefore, this article confirmed that the TPRM, through its TPRB, could not enforce specific obligations of the WTO Agreements to a reviewed member; in this case, the AoA's obligations to Indonesia.…”
Section: Indonesia's Trade Policy In the Agricultural Sector: Between...mentioning
confidence: 99%
“…In explaining the existence of TPRB, Kuenzel (2019) asserted that the TPRB Review could not be qualified as a product that effectively contributes to the reviewed member. The Annex 3A of the WTO Agreements confirms it by stipulating that: Therefore, this article confirmed that the TPRM, through its TPRB, could not enforce specific obligations of the WTO Agreements to a reviewed member; in this case, the AoA's obligations to Indonesia.…”
Section: Indonesia's Trade Policy In the Agricultural Sector: Between...mentioning
confidence: 99%
“…A recent paper on trade policy reviews (TPRs) by Karlas and Parízek (2019) shows that TPRs see active participation by members accounting, on average, for more than 95% of the reviewed members' trade volume. Another research from Kuenzel (2019) shows that interactions between Members at TPR meetings lead to subsequent higher bilateral trade flows, when countries involved are not too large. This paper focuses on the review process in the Committee on Agriculture (CoA) for two reasons: First, the CoA covers an area of negotiations under the Doha Development Agenda.…”
Section: Introductionmentioning
confidence: 99%